GOALS AND TASKS OF TEACHING ENGLISH TO PRIMARY CLASS STUDENTS - G. Narkabilova; Esonmirzayeva Madinabonu (Zeta Repository, 2023)
This article talks about the selection of modern educational methods that can be used to develop the motivation of primary school students to learn a foreign language outside the classroom.